Stakeholder management and entrepreneurship in Africa - Adomako, Samuel; Gyensare, Michael Asiedu; Ahsan, Mujtaba (Routledge, 2024)
"Building on past research in the broad field of stakeholder management and entrepreneurship, this book pushes a new agenda for more effective stakeholder engagement and management in entrepreneurial firms in Africa. Adomako, Gyensare, and Ahsan provide a novel lens for entrepreneurs to manage stakeholders in Africa, and a sense of current best practices. Issues discussed include how external stakeholders such as government, non-governmental organizations, media, civil society organizations, and local institutions influence the core business operations of entrepreneurial firms. The book confronts the central challenge of entrepreneurship by providing a comprehensive understanding of how entrepreneurs could identify, select, enrol, and coordinate stakeholders. In addition, it assesses issues such as stakeholder influence on corporate social responsibility strategy, sustainability, and environmental management of entrepreneurial firms. An essential read for postgraduate students, researchers, and public and private analysts"-- Provided by publisher.
Keywords: Industrial management -- Africa.; New business enterprises -- Africa -- Management.; Entrepreneurship -- Africa.; elektronické knihy; electronic books